PERAN BUDAYA ORGANISASI SEBAGAI MODERATOR DALAM HUBUNGAN ANTARA INFORMATION AND COMMUNICATION TECHNOLOGY DAN KNOWLEDGE SHARING TERHADAP KINERJA KARYAWAN (STUDI PADA PT PERKEBUNAN NUSANTARA I REGIONAL 8): PERAN BUDAYA ORGANISASI SEBAGAI MODERATOR DALAM HUBUNGAN ANTARA INFORMATION AND COMMUNICATION TECHNOLOGY DAN KNOWLEDGE SHARING TERHADAP KINERJA KARYAWAN (STUDI PADA PT PERKEBUNAN NUSANTARA I REGIONAL 8) - Faig Aizy, Fayadh; Bakhtiar, Fauziah; Nurmiati, Nurmiati (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study aims to examine the influence of information and communication technology, knowledge sharing, and organizational culture on employee performance at PT. Perkebunan Nusantara I regional 8. The data source in this study comes from primary data, where the data collection method uses interviews and questionnaires distributed to all employees of PT. Perkebunan Nusantara I regional 8. The sample used was 130 samples. The data analysis technique in this study used SMARTPLS 4 using software. The results of this study indicate that the variables of information and communication technology, knowledge sharing, and organizational culture have a significant effect on employee performance. The better employees share knowledge in technology, the higher the employee performance, the results of the data show that the variables of information and communication technology have a positive effect so that there is employee performance. And the relationship between information and communication technology with knowledge sharing on employee performance, this means that there is a relationship between information and communication technology, knowledge sharing, and organizational culture have a positive effect on employee performance.